Peramalan Curah Hujan Menggunakan Metode Jaringan Saraf Tiruan Dengan Optimasi Algoritma Bee Colony - I Putu Bagus Arya Pradnyana; Arief Andy Soebroto; Rizal Setya Perdana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
A high drop in rainfall can cause a disaster, so it is necessary to forecast to estimate how much rain will come. One of the main factors causing the flood disaster is the intensity of rainfall is very high, then the rainfall is still very interesting to continue to be studied. in this study made a system that can make forecasting using ANT method backpropagation with Artificial Bee Colony to determine the error rate of rainfall forecasting. In the performance test algorithm of Backpropagation-Bee Colony method showed that the average value of MSE showed the best result at iteration to 1000 that is MSE average of 0,0329. As for testing the accuracy of the 1000th iteration obtained an average MSE of 0.030 in December. The accuracy value in December amounted to 95%.